Assessment in special and inclusive education - Salvia, John; Ysseldyke, James E.;Bolt, Sara (Belmont, California : Wadsworth, Cengage Learning, 2013)
Assessment is a process of collecting information for the purpose of making important decisions about students. It is critical that those decisions be made both appropriately and fairly. Noted as the standard for professional resources in the field, ASSESSMENT offers basic assessment information along with a handbook-style reference of frank, comprehensive reviews of the tests most administered in K-12 schools. Featuring an emphasis on improved outcomes, the book equips teachers with the tools and knowledge to do assessments correctly as well as use assessment information to bolster student competence.
1. Assessment in social and educational contexts -- 2. Assessment and decision making in schools -- 3. Laws, ethical codes, and professional standards that impact assessment -- 4. Test scores and how to use them -- 5. Technical adequacy -- Part 2. Assessment in classrooms -- 6. Assessing behavior through observation -- 7. Teacher-made tests of achievement -- 8. Curriculum-based approaches to measuring student progress -- 9. Managing classroom management -- Part 3. Assessment using formal measures -- 10. Web chapter preview: how to evaluate a test -- 11. Assessment of academic achievement with multiple-skill devices -- 12. Using diagnostic reading measures -- 13. Using diagnostic mathematics measures -- 14. Using measures of oral and written language -- 15.Using measures of intelligence -- 16. Using measures of perceptual and perceptual-motor skills -- 17. Using measures of social and emotional behavior -- 18. Web chapter preview: using measures of adaptive behavior -- 19. Web chapter preview: using measures of infants, toddlers, and preschoolers -- 20.Web chapter preview: assessment of sensory acuity -- Part 4. special considerations in assessment -- 21. Using test adaptations and accommodations -- 22. Cultural and linguistic considerations -- 23. Using technology to help make assessment decisions -- 24. Multi-tiered system of supports (MTSS) and response to intervention (RTI) -- 25. Web chapter preview: using portfolios in assessment -- Part 5. Using assessment results to make educational decisions -- 26. Making instructional decisions -- 27. Making special education eligibility decisions -- 28. Making accountability decisions -- 29. Collaborative team decision making.
Includes bibliographical references and index.
Keywords: EDUCATIONAL TESTS AND MEASUREMENTS